2018
DOI: 10.1063/1.5037688
|View full text |Cite
|
Sign up to set email alerts
|

Gas breakdown in atmospheric pressure microgaps with a surface protrusion on the cathode

Abstract: Gas breakdown in atmospheric pressure microgaps with a cathode surface protrusion is highly sensitive to the protrusion geometry. The breakdown voltage is identified when the discharge enters the subnormal region, according to voltage-current curves calculated by a two-dimensional fluid model. The effects of the protrusion size and the aspect ratio on the gap breakdown voltage are examined. It is found that the protrusion size can have a more profound effect on the breakdown voltage than the protrusion's aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
0
14
0
3
Order By: Relevance
“…In fact, many previous studies concerning microdischarges have reported that the complicated surface geometry could distort the electric field in the gap, and thus affect the breakdown mechanism and discharge characteristics. Combined with the transition of discharge modes in DBD, which is extremely sensitive to the local field intensity, it is reasonable to predict that the rough surface may lead DBD from the diffuse mode to the filamentary mode, even under one set of parameters that has been proved to trigger a uniform DBD with smooth dielectric surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many previous studies concerning microdischarges have reported that the complicated surface geometry could distort the electric field in the gap, and thus affect the breakdown mechanism and discharge characteristics. Combined with the transition of discharge modes in DBD, which is extremely sensitive to the local field intensity, it is reasonable to predict that the rough surface may lead DBD from the diffuse mode to the filamentary mode, even under one set of parameters that has been proved to trigger a uniform DBD with smooth dielectric surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…One contributing factor could be the combination of various aspect ratio nonuniformities on the electrode causing an extended effective Paschen's curve. 21 The individual field emission parameters may also impact the transition from FE to PL, leading to the extended plateau, which can be investigated theoretically. One can mathematically predict the behavior of V b by coupling field emission with Townsend avalanche 22 and perform a matched asymptotic analysis to derive analytic equations in appropriate limits to demonstrate the transition between the two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the breakdown characteristics with a given electrode morphology, as well as designing engineered electrode surface structures with desired breakdown characteristics, is important to achieve targeted system variability in microdischarge devices. In our previous studies, 31,32 microgap breakdowns were investigated with the effects of a single surface protrusion which represents a small fraction of the electrode area, while here, the main focus is on the coupling effects of a collection of protrusions on the breakdown characteristics.…”
mentioning
confidence: 99%